Occurrence of dusky dolphin lagenorhynchus obscurus in Tierra Del Fuego archipelago over five decades - Dellabianca, Natalia Andrea; Torres, Monica Analia; Raya Rey, Andrea Nélida (Polar Biology)
Dusky dolphins Lagenorhynchus obscurus are distributed in circumpolar temperate and cold temperate waters of the Southern hemisphere. In Tierra del Fuego, their presence had been considered occasional but in the last decade, they became very common along the Beagle Channel. Here, we evaluate the occurrence of dusky dolphins in Tierra del Fuego along 44 years. We also discuss the relationship of this population with their distribution in southern South America. We used three different datasets: sightings hosted in the Ocean Biogeographic Information System OBIS, incidental sightings, and shipboard sighting surveys. A total of 44 sightings of dusky dolphins in Tierra del Fuego were obtained from the three datasets from 1972 to 2016. Most individuals were recorded in the southern area of the Fuegian Archipelago. Between the 1970s and 90s their occurrence in the Beagle Channel was infrequent up to the year 2000. From 2009 to date, they were recorded each year in the Argentinean Beagle Channel waters during austral summer and fall months, suggesting at least, a seasonal resident population. Our results preclude assessing if the observed groups of dolphins in the southern portion of South America came originally from the Atlantic or Pacific Oceans populations. Molecular and spatial ecology studies (e.g., using satellite tags) could help to better understand which lineage they belong to and their spatio-temporal movements in the area. Fil: Dellabianca, Natalia Andrea. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Provincia de Tierra del Fuego. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina Fil: Torres, Monica Analia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Provincia de Tierra del Fuego. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro ...